Reappraisal buffers the association between stress and negative mood measured over 14 days: implications for understanding psychological resilience - Johnson, Judith; O'Connnor, Daryl B.; Jones, Christopher; Jackson, Christopher; Hughes, Gareth J.; Ferguson, Eamonn (Wiley, 2016)
Reappraisal is thought to be an adaptive emotion regulation strategy, and research suggests that individuals who habitually reappraise report more positive patterns of affect overall. However, some experimental studies indicate that a greater tendency to reappraise can exacerbate stress response, and it is unclear whether reappraisal confers resilience or exacerbates response to naturally occurring stressors. In order to address this, the present study investigated whether reappraisal prospectively moderated the association between daily stressors and daily negative mood measured over 14 days. Participants (n = 236) completed a measure of reappraisal at baseline, before completing daily online entries of stress and positive and negative mood. Data were analysed using multilevel modelling. Results suggested that reappraisal moderated the association between stress and negative mood, such that higher levels of reappraisal were associated with lower levels of negative mood in response to stress. Moreover, higher reappraisal was also independently associated with lower levels of daily negative mood and higher levels of positive mood. These results suggest that higher reappraisal may confer resilience to stress.